Enseigner les sciences sociales pour éduquer le citoyen : une étude de cas sur l'histoire, la géographie et l'EDD - Sylvain Doussot; Josiane Grandjean
A lesson on sustainable development education in a last year primary classroom allows us to characterize the prevailing ideas that link disciplinary knowledge (here: history and geography) and social skills. The way the knowledge is used as an instrument to solve political questions has to do with the common practices in history and geography classrooms, and with traditional appraisal. By distinguishing appraisal and science as a problematised practice we can however highlight alternatives to help develop critical skills based on subject matter instruments. There is a lot at stake: on the one hand, to foster education to otherness that substitute the ability to understand choices people make to judgment, on the other hand, to replace showdown of solutions by the study of the value of statements in a debate.